1975
DOI: 10.1111/j.1365-4362.1975.tb00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Trichophyton Mentagrophytes Var. Gran. Infection to Man

Abstract: The occurrence of T. mentagrophytes var. gran. infection of small mammals in their natural habitat was studied. The most common host of the exoanthropic mammals was Clethrionomys glareolus (bank vole); the next most common hosts were hemisynanthropes Sorex araneus (common shrew) and eusynathropes Mus musculus (common mouse). Occurrence of infection increased during the winter months. Because small mammals gather in farm outbuilding during cold weather, man is more likely to be exposed to infection from them du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Similarly, human infections with T. gallinae were rarely reported in European countries during the last 35 years, e.g. in Sweden, Bulgaria, Russia, France and Spain, indicative of an apparently low if not neglectable pathogenic role of this zoophilic dermatophyte in Europe 9–14 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, human infections with T. gallinae were rarely reported in European countries during the last 35 years, e.g. in Sweden, Bulgaria, Russia, France and Spain, indicative of an apparently low if not neglectable pathogenic role of this zoophilic dermatophyte in Europe 9–14 …”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of small mammals in their natural habitat, T. mentagrophytes was isolated from 57 of 1288 animals representing 15 different species. The der matophyte was isolated most commonly from the bank vole (Clethrionomys glariolus), followed by the common shrew (Sorex araneus) and the common house mouse (M. musculus) (Chmel et al, 1975). In this survey, agricultural workers, exposed to these mammals in granaries and bams, risked con tracting T. mentagrophytes infection.…”
Section: A Reservoir and Incidencementioning
confidence: 91%
“…The dermatophytes are distributed worldwide and can involve a variety of small animal host species in addition to the mouse. Chmel et al (1975)conducted field studies in a wooded farm setting in Czechoslovakia and detected an overall prevalence rate of 4.4% (57 positive of 1288) for T. mentagrophytes infection in 6 of 13 species sampled; the prevalence in Mus musculus was 3.4%, with mice comprising 15.8% of the infections detected. Of the species that harbored the infection, all frequented the barn or granary area; the seasonal incidence was highest during the winter months when the rodent carriers were more likely to seek harborage indoors.…”
Section: Reservoir and Incidencementioning
confidence: 99%
“…Of the species that harbored the infection, all frequented the barn or granary area; the seasonal incidence was highest during the winter months when the rodent carriers were more likely to seek harborage indoors. Chmel et al (1975) also analyzed patient data and demonstrated that T. mentagrophytes was the predominant isolate from those who did agricultural work, while T. verrucosum was the main isolate from individuals who worked with farm animals. Also, human T. mentagrophytes infections were most common on the hands, wrist, forearm, face, and neck, unprotected skin sites readily contaminated by fodder, litter, or other materials while working in the barns.…”
Section: Reservoir and Incidencementioning
confidence: 99%